The correlation between organizational climate and employee’s job satisfaction: Results from Croatian enterprises - Perkov, Davor; Plećaš, Mihael; Marinović, Ana (Oeconomica Jadertina, 2025)
Organizational climate (OC) impacts and shapes employees’ performance, motivation, and job satisfaction (JS). This satisfaction stems from specific elements that affect the quality of an individual’s work life. The connection between OC and JS is intricate as it relates to every employee’s experience and its understanding. Numerous scientific studies indicate that the leadership style of managers plays a key role in creating JS. This paper examines the ways in which various dimensions of organizational culture (OC) relate to employee job satisfaction (JS) in Croatian companies, based on the primary hypothesis and five supplementary hypotheses. The initial section of the questionnaire pertains to a series of statements connected to the OC. Satisfaction served as a dependent variable, whereas the independent variables represented the five dimensions of the OC: “internal communication,” “enterprise structure,” “enterprise policy,” “employee’s advancement opportunities,” and “regard for employees’ personal interests”. An empirical study was carried out on a random selection of 100 employees from medium and large companies. The findings indicate that the relationship between OC and JS is mainly reflected in the “internal communication” aspect. Thus, enhancing “internal communication” is significantly linked to boosting employee JS in the chosen companies. No meaningful correlation was observed in the other four dimensions. The respondents highly rated their JS and the influence of their superior leaders on the chosen five dimensions. Due to the lack of sufficient empirical studies of this nature in Croatia and the surrounding region, the value of this work lies in its findings that are beneficial both to researchers and professionals. They can improve the design and execution of difficult changes to ensure a positive OC and JS. A relatively small size of the respondent sample and the demographic imbalance further restricted the general validity of the conclusions. In upcoming studies, the authors may explore additional statistical tests and further examine the connections between various forms of OC and specific industries and business operations.
Keywords: organizational climate, employee job satisfaction, internal communication, leaders’ influence